Effect of additives on the physical properties of steatite bodies - Tripathi U.C.; Agrawal G.N.; Joshi V.C. (My University, 2025)
The effect of tetravalent, divalent and monovalent additives on the physical properties of steatite bodies were studied at various temperatures (1300°-1400°C). Excellent electrical properties were exhibited by steatite compacts containing 1.5% Zr02 and Ti02 at 1400°C. © 1978, Taylor & Francis Group, LLC.